PERBEDAAN WAKTU TANGGAP TINDAKAN KEPERAWATAN PASIEN CEDERA KEPALA KATEGORI 1 – V DI INSTALASI GAWAT DARURAT RSUD DR. MOEWARDI - Haryatun, Nunuk; Sudaryanto, Agus (Universitas Muhammadiyah Surakarta, 2008)
Background: Head Trauma Patient in emergency care unit. Emergency need the which quickly. delay of head trauma treatment cause the handicap which remain to because damage of brain network or even generate the death. Very depended to and also the quality of [gift/ giving] [of] help to save the soul or prevent the handicap since in place occurence, on the way till hospital help . This Research aim to to know the time difference respon time the nursing care of head trauma lead the category I-V . Method: Sample taken by counted 60 patient by applying technique non probability. Appliance of data collecting in this research use the fundamental method in the form of observation. Data gathered in this research is later then analysed with the different test [of] mean. Result of: Research Result indicate that: ( 1) there are difference which signifikan time listen carefully the treatment action of wounded patient lead the category I V. Result of test anova obtain;get the f value accepted [at] level signifikansi 5%. ( 2) Time research listen action [of] [at] wounded patient lead the category I - V in RSUD Dr. inferential Moewardi Surakarta that terdaat of time difference listen carefully the treatment action at wounded patient categorize the I - II, III - IV, and IV - V, but to categorize the II-III do not show the existence of difference. This matter indicate that the each category of emergency condition of head trauma patient lead the category I - V need the different handling as according to requirement and condition of patient. (3) wounded Patient lead the category I obtain;get the longer treatment action (mean 98,33 minute) and wounded patient lead the category V obtain;get the quicker treatment action (mean 33,91 minute.